VALUASI EKONOMI PARIWISATA BAHARI DI PESISIR PANTAI DESA ANGSANA KECAMATAN ANGSANA KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Arwis Umar Gaib; Idiannor Mahyudin; Emmy Sri Mahreda (Universitas Lambung Mangkurat, 2017)
The purposes of this study are (1) to analyze the economic valuation of marine tourism in the coastal village of Angsana, Angsana District, Tanah Bumbu Regency, South Kalimantan (2) to be a Governmental recommendation for original income and marine tourism model in the coastal village of Angsana. Implementation of the study was conducted in the village of Angsana, Angsana District, Tanah Bumbu Regency, South Kalimantan province for one month (in April 2016). Calculating the value of the economic of the benefit of marine tourism of Angsana using travel cost method with an individual approach. Calculating the cost incurred for tourism activities. The number of visitors when the study was conducted has not known yet, so this study was done by using a non-probability sampling by setting the quota of 100 respondents. From the calculation of the number of visitors from January to April 2016 is as many as 26,719 visitors. Based on the calculation of a number of costs incurred every time a visitor travels to Angsana beach is Rp 4,118,00. Having obtained the number of visitors on years of study and the costs incurred per person when visiting Angsana beach, then it is calculated the economic valuation of marine tourism of Angsana beach. Based on the results of the calculation of the amount of the Economic Valuation of Angsana beach is in the amount of Rp 110,028,842,000. Angsana beach tourism is one of the tourists that presents the beauty of reef under the sea. There is an increasing number of visitors each year while the opening of the resort. For this reason, this marine coastal tourism could be one of the recommendations for the government in terms of raising revenue (the original income). In order to be sustainable in the future, Angsana beach should have a Tourism model in order to have an appeal and can attract the attention of visitors.